Reading for the love of God : how to read as a spiritual practice - Wilson, Jessica Hooten (Brazos Press, a division of Baker Publishing Group, 2023)
"An award-winning author shows us how to read as a spiritual practice in a way that encourages humility, increases our charity toward others, frees our minds and hearts from the trappings of contemporary idols, and directs us toward contemplation"--